Holistic Care of Women: Mind, Body, and Hormones - Prof. Dr. Syeda Batool Mazhar (Journal of Islamic International Medical College)
Doctors today practice allopathic medicine, an evidence-based system of care, where effective treatments are based on trials and studies. A scientific alternative system is osteopathic medicine, focusing on holistic approach by including mind and spirit in addition to the body. Homeopathic and Ayurvedic medicine are included in alternative therapeutic options with less support from the global scientific community.  Currently, in the developed countries, modern medicine is transitioning to client centered care and shared decision making in clinical practice. This is driven by the educated, well aware and discerning clients presenting in their clinics and hospitals.